Tax Reform and Debt Sustainability in Germany : An Assessment Using the Global Fiscal Model - Botman, Dennis (IMF Working Papers; Working Paper, 2007)
In 2005, the German government announced a far-reaching fiscal adjustment program. This paper uses the IMF's Global Fiscal Model to study its impact and explores options for addressing long-term pressures from population aging. The growth effects of the planned VAT increase are likely modest, largely owing to the stimulating effect of other tax reductions. The reform will improve the long-term debt path but achieving fiscal sustainability requires further adjustment over the medium term. An additional package of expenditure restraint, entitlement reform, and tax-base broadening compares favorably to other adjustment options. Spillover effects to trading partners of these policies are modest.